Interaction design beyond human-computer interaction - Sharp, Helen; Preece, Jennifer; Rogers, Yvonne (John Wiley & Sons, 2019)
Hugely popular with students and professionals alike, the Fifth Edition of Interaction Design is an ideal resource for learning the interdisciplinary skills needed for interaction design, human-computer interaction, information design, web design, and ubiquitous computing. New to the fifth edition: a chapter on data at scale, which covers developments in the emerging fields of 'human data interaction' and data analytics. The chapter demonstrates the many ways organizations manipulate, analyze, and act upon the masses of data being collected with regards to human digital and physical behaviors, the environment, and society at large. Revised and updated throughout, this edition offers a cross-disciplinary, practical, and process-oriented, state-of-the-art introduction to the field, showing not just what principles ought to apply to interaction design, but crucially how they can be applied.